Cloud Computing and Data Security : AWS and Google Case Study - Singh, Rajinder (International Journal of Computer Sciences and Engineering, 2019)
Cloud Computing is today’s exciting technology. Cloud computing means delivering various computer resources over the internet. Main examples of cloud services are webmail, social networking sites and business applications. Depending upon the services clouds can be divided into three categories SaaS, PaaS and IaaS. Depending upon the location clouds can be divided into four parts public, private, hybrid and community. Cloud security is very important to organization because data is very important to organizations as well as for the individuals. Depending upon the type of cloud and types of services, security is the two way responsibility. Security is responsibility of both the cloud service providers and users. Three major organizations which provide the cloud service are Azure, Google and AWS. This study discusses various features of Google Cloud and AWS with respect to security. Both these organizations give high priority to the security of user’s data. Both these organizations follow layer wise approach to protect user’s data. These organizations also provide their own build tools for security and privacy of the data.